Bone tuberculosis: epidemiological and hospital scenario in Brazil in the last 5 years (Research, Society and Development, 2023)
Tuberculosis (TB) is the leading cause of death from a single infectious agent in adults worldwide. Of this total, osteoarticular disease constitutes 10 to 20% of cases and 1 to 3% of all cases of tuberculosis. Thus, the aim of this study is to analyze hospitalizations for bone tuberculosis (TBO) in people between 40 and 80 years of age or older, in Brazil and its regions, in the last 5 years. This is a descriptive, retrospective and analytical study about hospitalizations due to TBO, elaborated through secondary data, in people between 40 and 80 years old or more, in the period from 2018 to 2022, in Brazil and its macro-regions. In the analyzed period, 242 hospitalizations for bone tuberculosis were registered, in people between 40 and 80 years old or more, in Brazil. With regard to geographic regions, the largest number of hospitalizations is concentrated in the Southeast region. Regarding age group, patients aged 50 to 59 years were the most affected. Regarding biological gender, males predominated, totaling 183 admissions. This research demonstrates that bone tuberculosis is a public health problem, subject to early diagnosis and preventive care.